Gambaran Pengetahuan tentang Anemia pada Remaja Putri di SMA Negeri 6 Kota Bengkulu - Rossy olivia gusfina (Jurnal Vokasi Keperawatan (JVK), 2022)
Adolescence is a developmental period of transition from childhood to adulthood, one of the diseases that affect a woman's health status is anemia. Anemia in young women is at a higher risk because young women experience menstruation every month, losing a lot of blood during menstruation, it is suspected that it can cause anemia and is in its infancy so that it requires more iron intake, someone who has a decreased immune system so that it is easy to get health problems. Lack of knowledge results in anemia problems experienced by young women will have a more serious impact. This study aims to determine the description of knowledge about anemia in adolescent girls at SMA Negeri 6 Bengkulu City with descriptive research methods. Adolescent students who participated in this study amounted to 82 respondents, sampling using accidental sampling technique. Collecting data using a questionnaire with 25 questions. The results of this study can be concluded that from 82 respondents with good knowledge of the category as many as 41 students (50%), the suggestions from this study can be used as input and reference in conducting further research on anemia with different variables.